Prevention and Treatment of Influenza, Influenza-Like Illness, and Common Cold by Herbal, Complementary, and Natural Therapies - Haider Abdul-Lateef Mousa MBChB, MSc (SAGE Publishing, 2017)
In recent years viral respiratory tract infections, especially influenza viruses, have had a major impact on communities worldwide as a result of unavailability of effective treatment or vaccine. The frequent alterations in the antigenic structures of respiratory viruses, particularly for RNA viruses, pose difficulties in production of effective vaccines. The unavailability of optimal medication and shortage of effective vaccines suggests the requirement for alternative natural therapies. Several herbal remedies were used for prevention and treatment viral respiratory illnesses. Among those that were found effective included maoto, licorice roots, antiwei, North American ginseng, berries, Echinacea, plants extracted carnosic acid, pomegranate, guava tea, and Bai Shao. There is scientific evidence regarding the effectiveness of several complementary therapies for colds. Oral zinc may reduce the length and severity of a cold. Taking vitamin C supplements on a regular basis only slightly reduces the length and severity of colds. Probiotics were found better than placebo in reducing the number episodes of acute upper respiratory tract infections, the rate of episodes of acute upper respiratory tract infection and reducing antibiotic use. Alkaline diets or drinks might have antiviral properties as in vitro studies demonstrated inactivation effect of alkaline medium on respiratory virus. Earthing might have a natural anti-inflammatory effect for human body. It is now accepted that an overwhelming inflammatory response is the cause of human deaths from avian H5N1 influenza infection. Earthing accelerates immune response following vaccination, as demonstrated by increases of gamma globulin concentration. No in vivo or clinical studies were found that investigate the role of alkalization or earthing on respiratory viral infections. Thus, future studies are recommended to reveal any potential curative effects.